Effect of Instructional Program on Knowledge Regarding Vulvovaginal Candidiasis Among Female University Students - Amel Dawod Kamel Gudia; Abeer Saad Eswi; Azza Ali Abd El hamid; Soumaya Mohamed Hassan (GLOBAL HEALTH SCIENCE GROUP, 2019)
Adolescents learn about Vulvo vaginal candidiasis (VVC) because its common clinical problem in female during this age throughout the world particularly in hot, subtropical climates. Annually in the United States there are approximately 13 million cases of vulvo vaginal candidiasis (VVC), resulting in 10 million gynecologic office visits per year. It is estimated that 75% of women will experience at least one episode in their lifetime, with a projected 50% of all female experiencing multiple episodes (Kamath, etal , 2014). Education in health is one of the key components of primary health care and one of the most vital health care requirements for female that must be considered much more in the primary health care system, particularly maternal and child health. Moreover Knowledge of how to prevent vaginal Candidiasis could save many female from frequent office visit, uncomfortable vaginal infections and prevent complications of it (Gilson, 2012). To assess the knowledge of female university students about (VVC) and examine the effect of instructional program on their knowledge regarding Vulvovaginal Candidiasis among female university students. A quasi-experimental design